Social workers’ intervention during natural hazards - Matlakala, Frans K.; Makhubele, Jabulani C.; Nyahunda, Louis (AOSIS, 2022)
Social work profession is anchored on theory and practice and has both primary and secondary methods of interventions. The knowledge base of social work is constituted by values, principles, theories, skills and techniques. Globally, social work scholars have developed paradigms, theories, approaches, perspectives, models, techniques, skills and principles that could be applied in a variety of settings to various social ills for the benefit of clients in communities. Thus, this study was aimed at exploring social workers’ intervention during natural hazards. The researchers used an interpretative qualitative research approach and case study design. Moreover, five social workers who provide psychosocial counselling and social relief of distress were purposively sampled to participate in this study. Data were collected through individual semi-structured interviews and analysed thematically. The study found that social workers use three primary methods of social work: casework, group work and community work. Furthermore, the participants stated that they play roles such as educator, counsellor and broker when dealing with victims of natural hazards. Based on the findings, the researchers have noted that not all social workers are active in providing psychosocial counselling to the victims of natural hazards. As such, the researchers recommend more workshops to educate all social workers that social workers have an important role to perform in the midst of natural hazards.
Jàmbá - Journal of Disaster Risk Studies
Keywords: Natural hazards; Social workers; Methods; Roles; Intervention; Hazard mitigation; Social workers -- South Africa